Increasing efficiency and sustainability: A comparative analysis of concrete 3D printing and traditional methods based on case studies - Karamara Merve; Bogdanski Moritz-Ole; Zöller Raphael; Albrecht Sophie Viktoria; Linner Thomas; Bock Thomas; Braml Thomas (MATEC Web of Conferences)
At the forthcoming Concrete Solutions 2025 conference, the subject of concrete 3D printing will be explored in the “Case Studies” category, with a comparison to traditional methods. Concrete 3D printing offers several significant advantages, including the ability to create complex geometries, increased material efficiency, faster build times and cost savings. These are particularly important in the context of the current skilled labour shortage and emphasis on resource efficiency in construction. Nevertheless, challenges persist in the areas of machine reliability, process integration, and material adaptation to meet the requirements of 3D printing. The case studies will present modular and design-engineering-based strategies for the development of efficient, scalable automation solutions that integrate 3D printing into existing processes and allow for project-specific customisation through selective automation. These findings provide a robust framework for industrial applications that enhance efficiency and adaptability. By comparing concrete 3D printing to conventional methods, the insights offer a foundation for advancing automated production in construction, promoting scalable, resource-efficient, and economically sustainable practices that address the industry’s evolving demands.